The Influence of Leadership in Academia on The Standard of Teaching in Malaysian Private Universities - Gopal Nair, Shanti; Mohamed Sa’dom, Nur Zulaikha; Mat Yusoff, Siti Haryani; Altounjy, Rana (International Journal of Academic Research in Progressive Education and Development, 2023)
The purpose of this research is to analyse the role played by academic leaders in improving the teaching quality in Malaysian private universities. As the future of the country’s economic growth is dependent on the quality of education offered by private universities, focusing on teaching quality can improve the future of Malaysian students and determine the sustainability of private universities. The target population was academicians from three private universities in Nilai, Malaysia. This study employed a qualitative research approach. The thematic method was utilised to analyse data which was gathered through an in-depth interview with seven lecturers. In addition to that, an in-depth understanding of the subject matter was obtained through literature reviews. The findings of this study show that academic leaders play a key role in increasing the motivation level of lecturers to improve the quality of education provided in private universities. Respondents assert that academic leaders need to provide a clear definition of goals, conduct regular performance evaluations, elevate credibility by mentoring, and present rewards for good teaching quality. This study raises an opportunity for future researchers to study the challenges faced by academic leaders in improving the quality of teaching in private universities. Another beneficial research would be to conduct an analysis of leadership practices in private universities which are financially stable and progressing well.